Corporate social responsibility by the Malaysian telecommunication firms - Abdul Hamid, Fathilatul Zakimi; Atan, Ruhaya (Center for Promoting Ideas (CPI), USA, 2011)
Prior Corporate Social Responsibility (CSR) studies in Asia suggest that CSR practices in many Asia countries are lag behind the Western countries.In addition, factors such as greater social expectations on business responsibility and the development of governance systems that will influence firm’s CSR practices. As noted by Gray et al. (2002) that cultural and national differences are likely the factors affect the CSR practices.The Malaysian Security Commission viewed CSR as part of the corporate governance in the essence of CSR will strengthen the framework on good governance i.e. by considering the wider interests of others stakeholders such as employees, consumer and the society at large.The purpose of this study is to examine the relationship between the level of CSR disclosure and the nature of companies’ ownerships from the year 2002 until 2005.The levels of companies’ ownership are divided into local, government and foreign ownerships in the three Malaysian telecommunications companies.This study adopted the same instruments used in prior CSR studies in measuring firm’s CSR disclosure.The CSR disclosure level employ in this study is the proxy for firm’s CSR activity.The finding from this study indicates that the CSR disclosure level is increased moderately during the period under study. On the other hand, at the disclosure level themes, it shows some variability’s on the amount of CSR information’s disclosed by the firm’s and this could be related to the firm ownership’s structure.